EMPLOYEE RESISTANCE MANAGEMENT IN THE PROCESS OF BUREAUCRATIC SIMPLIFICATION AT THE REGIONAL OFFICE OF THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE IN NORTH SUMATRA - Fathurohman; Nazaruddin; Isfenti Sadalia (RADJA PUBLIKA, 2026)
This study aims to analyze factors influencing employee resistance in the bureaucratic simplification process at the Regional Office of the Directorate General of Customs and Excise in North Sumatra. This reform aims to create a more agile and responsive organization. However, it triggers both positive and negative responses from employees. A quantitative approach was applied with 141 respondents. Variables include communication, participation, resources, transformational leadership, trust in management, future clarity, and organizational justice. The findings reveal that participation, trust in management, future clarity, and organizational justice significantly affect resistance to change. Furthermore, trust and future clarity act as mediating variables between resources and resistance. These findings highlight the importance of transparency, fairness, and employee involvement in change management strategies.